First-line chemotherapy for advanced ovarian cancer: paclitaxel, cisplatin and the evidence - Sandercock, J; Parmar, MKB; Torri, V (Springer Nature, 1998)
As of June 1998, four randomized trials have been completed comparing the combination of paclitaxel and cisplatin with a cisplatin-based control arm. The results of three of these trials are available; one has been published as a full paper, the other two in abstract form only. Two of the reported trials (GOG-111 and the Intergroup trial) provide clear evidence that cisplatin combined with paclitaxel is a more effective regimen than one using the same dose of cisplatin combined with cyclophosphamide. The results of the third reported trial (GOG-132) are rather different, suggesting that a higher dose of single-agent cisplatin may be as effective as the paclitaxel/cisplatin combination tested in the other two trials. A number of explanations for these unexpected results have been proposed: false-positive results in GOG-111 and the Intergroup trial; false-negative results in GOG-132; high crossover in GOG-132 (including crossover before progression); the cyclophosphamide in the control arm of GOG-111 and the Intergroup trial had a negative impact on outcome in the control group in these trials; the higher dose of cisplatin when used as a single agent in GOG-132 had a positive impact on outcome for the control group in this trial. These explanations are discussed in detail, and their implications explored.